REPRESENTATION OF VIOLENCE TOWARD WOMEN IN SERBIAN PRESS - Necić, Neda N (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2019)
In order to understand how print media report on violence toward women, the research was conducted on the corpus of five issues of daily newspapers: Kurir, Blic, Danas, Večernje novosti and Politika. The research was method was quantitative and qualitative content analysis, as a comparative analysis of two periods: the first period covered 25.11.2017 - the International Day for the Elimination of Violence Against Women, and the second period was from 19.03.2018. until 25.03.2018. We have established that journalists do not pay enough attention to the problem of violence toward women, and in their reporting they do not comply with the norms prescribed by the Code of of Journalists Conduct in Serbia. We have also found that the media representation of violence toward women was structured through recognizable reporting matrices based on stereotypes and sensationalistic approach. The results of the first research period - the International Day for the Elimination of Violence Against Women, point to the fact that the fight against the problem of violence toward women is only declarative, because even on the very day dedicated to the elimination of violence, journalists lack the interested to write about it, and their reports are not adjusted and adequate. The results of the second, randomly selected research period were relatively similiar.